2013
DOI: 10.1182/blood-2012-07-445197
|View full text |Cite
|
Sign up to set email alerts
|

Emergence, origin, and function of neutrophil–dendritic cell hybrids in experimentally induced inflammatory lesions in mice

Abstract: Key Points Neutrophils differentiate into neutrophil–dendritic cell hybrids upon recruitment to sites of inflammation or infection. Hybrids play dual protective roles against bacterial infection by rapidly clearing bacteria and presenting bacterial antigens to T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 48 publications
3
102
0
Order By: Relevance
“…98% of the IFN-g-expressing cells in lung digests are neutrophils, as marked by high expression levels of Ly6G. Recent reports have indicated that CD11c-expressing neutrophils arise during inflammation and may be important in bacterial clearance and antigen presentation by functioning as neutrophil-dendritic cell hybrids (39,40). The number of lung cells coexpressing CD11c and Ly6G was greater in WT mice with S. pneumoniae pneumonia compared with those given PBS (4.0 6 0.73 3 10 4 versus 0.13 6 0.04 3 10 4 [n = 4]; P , 0.05 using t test).…”
Section: Resultsmentioning
confidence: 99%
“…98% of the IFN-g-expressing cells in lung digests are neutrophils, as marked by high expression levels of Ly6G. Recent reports have indicated that CD11c-expressing neutrophils arise during inflammation and may be important in bacterial clearance and antigen presentation by functioning as neutrophil-dendritic cell hybrids (39,40). The number of lung cells coexpressing CD11c and Ly6G was greater in WT mice with S. pneumoniae pneumonia compared with those given PBS (4.0 6 0.73 3 10 4 versus 0.13 6 0.04 3 10 4 [n = 4]; P , 0.05 using t test).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, neutrophils were recently shown to differentiate into ''neutrophil-DC hybrids'' that express markers typical of both neutrophils and DCs [81,82]. Of note, those intermediate cells exhibit a blend of neutrophil features such as phagocytosis, release of neutrophil extracellular traps and bacterial killing, and APC properties including DC-like morphology and migration, cytokine production and antigen presentation to naive CD4 + T cells.…”
Section: Interaction With Neutrophils: Unexpected Generation Of Apclimentioning
confidence: 99%
“…As a result of this crosstalk, neutrophils receive potent signals that trigger a substantial extension of their life span and allow them to acquire distinct phenotypes and functions including the capacity to facilitate monocyte differentiation and DC maturation, and to interact with T cells [78][79][80]. It is this intriguing APC-like aspect of neutrophil biology that is most relevant to this review.In mice, neutrophils were recently shown to differentiate into ''neutrophil-DC hybrids'' that express markers typical of both neutrophils and DCs [81,82]. Of note, those intermediate cells exhibit a blend of neutrophil features such as phagocytosis, release of neutrophil extracellular traps and bacterial killing, and APC properties including DC-like morphology and migration, cytokine production and antigen presentation to naive CD4 + T cells.…”
mentioning
confidence: 99%
“…96 On the other hand, has been described that neutrophils can have a APC-like phenotype expressing costimulatory molecules and activating CD4 C T cells polarizing to a TH1/ TH17 phenotype in inflammatory mouse model, but for hRSV infections this phenomenon has not been demonstrated yet. 97,98 This could be an important unexplored area because has been described that hRSV can infect human neutrophils. Indeed, it has been possible to measure F, G and N proteins and viral RNA on those cells, 99 suggesting that neutrophils can uptake virus in the airways of infected children and then present antigens to T cells, but further evidence is necessary to support this idea.…”
Section: An Adequate Cd4mentioning
confidence: 99%